TERRAIN: FETAL GROWTH TELEHEALTH SYSTEM BASED ON 2D FETAL HEAD IMAGE USING RANDOMIZED HOUGH TRANSFORM - Robeth Rahmatullah; Ikhsanul Habibie; Petrus Mursanto; Sani Muhammad Isa (Jurnal Ilmu Komputer dan Informasi, 2014)
Abstract Intrauterine growth restriction (IUGR) is one of many fetal abnormalities, which has high contribution on maternal mortality rate and perinatal mortality rate in Indonesia. Apparently, IUGR impact can be reduced if only the symptoms are detected earlier and the correct treatment is applied. However, fetal growth detection and monitoring process in Indonesia is obstructed because the number of physicians is very limited and ultrasonography (USG) devices are expensive. Moreover, both the physicians and USG devices are only available in big cities. To answer those problems, this research proposed an intelligent system that can provide fetal growth telemonitoring in rural areas. This system consists of three components: portable USG device, mobile application which is developed using Android operating system, and server application which is developed using Django. The main feature of this system is automatic fetal head parameter detection and its ability to operate in the limited internet access environment. In this system, automatic fetal head parameter detection uses RHT method to approximate fetal headâ€™s ellipse shape. Experiment result shows that RHT detection ability with âˆ†ellipse average of 79.564 and running time average of 0.373 second.